BOLIVAR’S AND URDANETA’S CENTENNIAL (1883-1888). ZULIA’S PEOPLE’S ANSWER TO THEIR STRUGGLE TO RESCUE THE STATE POLITICAL AUTONOMY. (Tzintzun, Revista de Estudios Históricos, 2016)
Simon Bolivar and Rafael Urdaneta were the most outstanding heroes of VenezuelaIndependence War, which took place between 1880 and 1888. Bolivar’s andUrdaneta’s one hundredth birthday anniversary was used to strengthen the notionof Venezuelan Nation. This celebration was held within a political crisis duringwhich the elite and the people of Maracaibo struggled to consolidate a feeling ofnation by a sense of belonging both locally and regionally. This struggle was theanswer to Guzman Blanco’s government against Zulia’s autonomy. The organizationof the centennial made it possible to create an image of progression of the regionand it also gave it the necessary merits to make a living as an independent entity.
Keywords: Native holidays(parties); centenary; 19th century; Zulia; Venezuela; Simon Bolivar; Rafael Urdaneta